A variant of Kounis syndrome due to diclofenac sodium - Alagesan, Arun Kumar; R., Kannan; Sriharsha, Tirumalasetty; V., Vikrannth; J., Raghav; Raghavan, Vinod; Reddy, Monika (International Journal of Advances in Medicine, 2023)
Kounis syndrome is an acute coronary syndrome of varying degrees induced by allergic or anaphylactic reaction leading to coronary vasospasm or atheromatous plaque erosion or rupture or global myocardial hypoperfusion occurring as a result of systemic vasodilation and decreased venous return in context of anaphylaxis. We reported a case of 33-year-old female who presented to emergency department in an irritable state with complaints of nausea, vomiting, abdominal pain, breathlessness and generalized itching which developed secondary to administration of diclofenac injection by intra muscular (IM) route. On evaluation, echocardiography revealed global LV systolic dysfunction. The patient was successfully treated with continuous noradrenaline infusion, fluid resuscitation and other supportive measures with repeat echocardiography revealing normal LV systolic function.